Horse ooplasm supports in vitro preimplantation development of zebra ICSI and SCNT embryos without compromising YAP1 and SOX2 expression pattern - Gambini, Andrés (2020)
Fil: Gambini, Andrés. Universidad de Buenos Aires. Facultad de Agronomía. Departamento de Producción Animal. Cátedra de Producción Equina. Buenos Aires, Argentina. - CONICET. Buenos Aires, Argentina.